Brief and extended abstinence from chronic oral methylphenidate treatment produces reversible behavioral and physiological effects. Issue 2 (27th August 2019) - Kalinowski, Leanna; Connor, Carly; Somanesan, Rathini; Carias, Emily; Richer, Kaleigh; Smith, Lauren; Martin, Connor; Mackintosh, Macauley; Popoola, Daniel; Hadjiargyrou, Michael; Komatsu, David E.; Thanos, Panayotis K.
Abstract: Methylphenidate (MP) is a commonly prescribed psychostimulant to individuals with Attention Deficit Hyperactivity Disorder, and is often used illicitly among healthy individuals with intermittent breaks to coincide with breaks from school. This study examined how intermittent abstinence periods impact the physiological and behavioral effects of chronic oral MP self‐administration in rats, and whether these effects persist following prolonged abstinence from the drug. Rats were treated orally with water, low‐dose (LD), or high‐dose (HD) MP, beginning at PND 28. This daily access continued for three consecutive weeks followed by a 1‐week abstinence; after three repeats of this cycle, there was a 5‐week abstinence period. Throughout the study, we examined body weight, food intake, locomotor activity, and anxiety‐ and depressive‐like behaviors. During the treatment phase, HD MP decreased body weight, food intake, and depressive‐ and anxiety‐like behaviors, while it increased locomotor activity. During intermittent abstinence, the effects of MP on locomotor activity were eliminated. During prolonged abstinence, most of the effects of HD MP were ameliorated to control levels, with the exception of weight loss and anxiolytic effects. These findings suggest that intermittent exposure to chronic MP causes physiological and behavioral effects that are mostly reversible following prolonged abstinence.